Exposures influencing total IgA level in colostrum. (21st September 2015) - Munblit, D.; Sheth, S.; Abrol, P.; Treneva, M.; Peroni, D. G.; Chow, L.-Y.; Boner, A. L.; Pampura, A.; Warner, J. O.; Boyle, R. J.
Abstract : Immunoglobulin A (IgA) is a predominant immunoglobulin present in human breast milk and is known to play an important role in infant gut immunity maturation. Breast milk composition varies between populations, but the environmental and maternal factors responsible for these variations are still unclear. We examined the relationship between different exposures and levels of IgA in colostrum. The objective of this study was to examine whether exposures analysed influence levels of IgA in colostrum. The present study used 294 colostrum samples from the MecMilk International cohort, collected from women residing in London, Moscow and Verona. Samples were analysed in automated Abbott Architect Analyser. We found an inverse correlation between time postpartum and colostrum total IgA level ( r =−0.49, P <0.001). Adjusting for maternal parity, smoking, fresh fruit and fish consumption and allergen sensitization, multiple regression model showed that IgA levels were influenced by colostrum collection time ( P <0.0001) and country of collection ( P <0.01). Mode of delivery influence did not appear to be significant in univariate comparisons, once adjusted for the above maternal characteristics it showed a significant influence on total IgA ( P =0.01). We conclude that the concentration of IgA in colostrum drops rapidly after birth and future studies should always consider this factor in analysis. IgA concentration varied significantly between countries, with the highest level detected in Moscow and lowest in Verona. Mode of delivery effect should be confirmed on larger cohorts. Further work is needed to determine ways to correct for IgA decline over time in colostrum, and to find the cause of variations in IgA levels between the countries.